2000
DOI: 10.1177/002215540004801108
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Transcription Factor AP-1 Family Proteins in Ameloblast Nuclei of the Rat Incisor

Abstract: We examined by immunocytochemistry the localization of the AP-1 family proteins c-Jun, JunB, JunD, c-Fos, FosB, Fra-1, and Fra-2 in rat incisor ameloblasts. Most of the antibodies against AP-1 family proteins, except for c-Fos-specific antibody, labeled ameloblast nuclei. The labeling intensity of the c-Jun, JunD, and Fra-2 antibodies was stronger than that of JunB, FosB, and Fra-1. Antibody reactivities of c-Jun, JunD, and Fra-2 were greatly enhanced during or after the transition zone. Furthermore, c-Jun ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
3
11
1
Order By: Relevance
“…In contrast, anti-p-ATF2 labeling without the blocking peptide exhibited positive nuclear reactivity in the late secretion ameloblasts (c). Bars,50 µm. in the maturation zone c-Jun, JunD and Fra2 are the predominant AP-1 family proteins, as described earlier (Nishikawa, 2000). Anti-ATF2 antibodies uniformly labeled nuclei of ameloblasts and other enamel organ-derived cells from the proliferation to maturation zones.…”
Section: Discussionsupporting
confidence: 75%
“…In contrast, anti-p-ATF2 labeling without the blocking peptide exhibited positive nuclear reactivity in the late secretion ameloblasts (c). Bars,50 µm. in the maturation zone c-Jun, JunD and Fra2 are the predominant AP-1 family proteins, as described earlier (Nishikawa, 2000). Anti-ATF2 antibodies uniformly labeled nuclei of ameloblasts and other enamel organ-derived cells from the proliferation to maturation zones.…”
Section: Discussionsupporting
confidence: 75%
“…The present study showed that CBP did localize in the nuclei of the ameloblasts mostly in maturation zone, whereas the possibility exists that loss of cytoplasmic CBP occurred during long sample incubation time in a EDTA solution for demineralization. Considering that c-Jun labeling is strong in the maturation zone (Nishikawa 2000), it is reasonable to speculate that CBP and c-Jun interact with each other, directly or indirectly, although the localization of CBP and c-Jun was complementary in some specimens in this study and this study did not provide any evidence suggesting any interactions of two proteins. Furthermore, CBP was also detected in the nuclei of enamel organ-derived cells other than ameloblasts.…”
Section: Discussioncontrasting
confidence: 61%
“…They are referred to as ruffle-ended ameloblasts (RA, major cell appearance with ruffled border at apical cell end) and smooth-ended ameloblasts (SA, minor cell appearance occupying one fifth of the total maturation zone) (Josephsen and Fejerskov 1977). Moreover, c-Jun labeling is stronger in RA than in SA (Nishikawa 2000). A large part of RA is considered to contribute to mineral uptake in the enamel matrix, although SA contributes to some passive calcium uptake (Reith and Boyde 1981;Takano et al 1982).…”
mentioning
confidence: 99%
“…AP-1 components are specific for some biological processes including cellular proliferation, differentiation, apoptosis and oncogenic transformation that are identified as a proto-oncogene (Ovitt and Rüther 1989;Nishikawa 2000;Srouji et al 2005). Particularly, c-fos has been associated with the coordinated regulation of gene expression during cellular proliferation and differentiation (Stachowiak et al 1990;Bakiri et al 2002).…”
Section: Wisletmentioning
confidence: 99%